From Classroom to Field: Filipino Students' Internship Reflections at Universitas Pamulang - Diyah Iis Andriani; Haryati Haryati (VELES Voices of English Language Education Society, 2023)
The study aims to examine Philippine students’ experiences on internship program in Universitas Pamulang. It focuses on the discriminative experiences among interns: opportunities and challenges. In this study, the writers apply descriptive qualitative research method with case study design by conducting a semi-structured interview and distributing questionnaires to 6 Philippine students having participated in internship program. The interns need to share the opportunities and challenges during and after the internship activity. Further, the interns need to share how they cope the challenges. The findings indicate that the interns present homogenous and motivated opportunities, challenges, and ways out of internship program. In opportunity aspects, the results indicate the interns obtain more work experiences during the program. Interns are able to improve their skills and teaching performance, learn new language, culture, and tradition, and prepare for their future careers. However, results indicate the interns experience language, technological and technical barriers as their challenges as they have to do the whole activities through online. Therefore, the interns should find some ways to solve their problems, namely by expanding understanding and patience, discovering interesting and effective ways of learning, and communicating with supervisors. The activities in internship program assist interns to be skillful in handling any kinds of situations.